Takotsubo syndrome and atrial myxoma—identifying a new trigger: a case report - Velarde-Acosta, Kevin; Sandoval, Robert; Falcón-Quispe, Luis; Anicama Lima, William Efrain; Baltodano-Arellano, Roberto (Frontiers in Cardiovascular Medicine, 2024)
Takotsubo syndrome (TTS) is a rare cardiomyopathy, but its prevalence is increasing due to the greater availability of diagnostic tools, whose pathophysiology is unknown; however, the evidence points to an excess of catecholamines that ends up generating cardiac stunning. The cause of excessive sympathetic discharge is multifactorial, and some tumors may be related to their origin. In this case report, we present a female patient with TTS whose only identified triggering factor was an atrial myxoma, which generated an unusual clinical presentation. Current multimodal diagnostic tools together with the multidisciplinary evaluation of the HeartTeam allowed an accurate diagnosis and an adequate management of the clinical picture.